Stenting of hypoplastic aortic segments with mild pressure gradients and arterial hypertension. Issue 11 (27th April 2006) - Boshoff, D; Budts, W; Mertens, L; Eyskens, B; Delhaas, T; Meyns, B; Daenen, W; Gewillig, M
Abstract : Objective: To determine the safety, feasibility and effectiveness of stent expansion of hypoplastic aortic segments with pressure gradients in patients with arterial hypertension. Design: Non-randomised prospective clinical trial. Setting: Tertiary referral centre, congenital cardiac unit. Patient selection: 20 consecutive patients (median age 14.5 years, range 11.6–38.8 years) with arterial hypertension and a hypoplastic segment of the aorta. Seventeen patients had successful previous arch interventions in a coarctation site. Interventions: Stent deployment in hypoplastic arch segments. Main outcome measures: Gradient across the aortic arch; complications early and during follow up; residual hypertension. Results: 23 stents were deployed: 13 in the cross and 10 in the isthmus. The mean gradient across the aortic arch decreased from 16 (SD 6) (median 17) to 3 (4) (median 1) mm Hg (p < 0.001). In a few patients a mild gradient persisted just distal to the left carotid artery due to residual orificial narrowing or acute angulation. No complications occurred during or after the procedure. During follow up of 2.2 years (range 0.2–4.8 years) arterial hypertension resolved in 10 patients and 10 required residual drug treatment with better control of blood pressures. Conclusions: Pressure loss due to residual hypoplastic aortic segments can be treated effectively and safely with stent expansion. Some patients remain mildly hypertensive and require additional drug treatment.